How to make more people adopt healthy behaviors? Assessing health literacy, health promoting lifestyle and their association of community residents in Shenzhen, China - Zhang, Lei; Liao, Jia; Pan, Xueyan; Liang, Dongmei; Zeng, Jinmei; Sun, Mingwei; Luo, Xiaowen; Ma, Xingyu; Yin, Mingjuan; Ni, Jingdong (Frontiers in Public Health, 2022)
Introduction Health literacy (HL) has been concerned a key factor for determining the use of health information and promoting health. The study aimed to explore the relationship between different health literacy types and health promoting lifestyle (HPL) in different health literacy population. Methods The survey analyzed a sample of 16,921 community residents in Shenzhen. The Chinese Citizen Health Literacy Questionnaire and health-promoting lifestyle profile II (HPLP- II) were used to assess health literacy and health promoting lifestyle. Results Participants were divided into different populations based on the correlation between HL and HPL. The low-HL and medium-HL populations were judged to lack health literacy, and demographic characteristics were significantly different between different HPL levels in low-HL and medium-HL populations. There were 6 types of HL, and health information literacy (β = 0.08, P < 0.001) and chronic disease literacy (β = 0.08, P < 0.001) positively predicted HPL in the low-HL population. In the medium-HL population, the results of reward and punishment analysis showed that health information was a basic factor, chronic disease was performance factor, medical care was a motivating factor for HPL; there were 6 dimensions of HPL, and health responsibility (HR), stress management (SM) and physical activity (PA) were not significantly different in medium-HL population. The results of regression analysis showed that HR and PA had a great impact on HPL (HR: β = 0.193, PA: β =0.179, β for other dimensions was 0.186, 0.176, 0.171, 0.164), but the HR and PA standardized scores were lowest in the HPL dimensions (HR: 69.42, PA: 68.5, lower than other dimensions), so it may be HR and PA that cause HPL unchanged between groups in the medium-HL population. Conclusions Different HL levels have different relationships with HPL, and different HL types have different effects on HPL. Shenzhen community residents need to improve their HL, and they have great potentials for further progress to improve the population health. Public health policy makers need to consider formulating different policies for people with different HL levels.